Ludwig’s angina - an emergency complication arising from delayed dental treatment: The experience in a Nigerian tertiary institution - Thomas Owobu; Edugie Ekuase; Oba O. Azah; Sulaiman S. Adamu; Babatunde O. Bamgbose (DiscoverSys Inc., 2020)
Objective:Â The aim of this paper was to report two cases and management of Ludwigâ€™s angina in a Nigerian tertiary health facilty.Methods:Â Ludwigâ€™s angina is anÂ acute onset,Â potentially life-threatening surgical emergency in young adults that presents with rapidly expanding, diffuse inflammation of the submandibular and sublingual spaces, mostly from odontogenic infections.Results:Â One of the sequelae is airway compromise. Given the sparse health facilities and poor access to health,Â we observed an increasing rate of Ludwigâ€™s angina secondary to odontogenic infections in our practice. We present two cases of Ludwigâ€™s Angina arising from delayed dental treatment.Conclusion:Â Socioeconomic status and unrest due to insurgency have hampered early presentation and management